Adapting Patient and Public Involvement processes in response to the Covid‐19 pandemic - Claire Snowdon; Elizabeth Silver; Paul Charlton; Brian Devlin; Emma Greenwood; Andrew Hutchings; Susan Moug; Ravinder Vohra; Richard Grieve (Wiley, 2023)
Abstract Background The COVID‐19 pandemic brought rapid and major changes to research, and those wishing to carry out Patient and Public Involvement (PPI) activities faced challenges, such as restrictions on movement and contact, illness, bereavement and risks to potential participants. Some researchers moved PPI to online settings during this time but remote consultations raise, as well as address, a number of challenges. It is important to learn from PPI undertaken in this period as face‐to‐face consultation may no longer be the dominant method for PPI. Methods UK stay‐at‐home measures announced in March 2020 necessitated immediate revisions to the intended face‐to‐face methods of PPI consultation for the ESORT Study, which evaluated emergency surgery for patients with common acute conditions. PPI plans and methods were modified to all components being online. We describe and reflect on: initial plans and adaptation; recruitment; training and preparation; implementation, contextualisation and interpretation. Through first‐hand accounts we show how the PPI processes were developed, experienced and viewed by different partners in the process. Discussion and Conclusions While concerns have been expressed about the possible limiting effects of forgoing face‐to‐face contact with PPI partners, we found important benefits from the altered dynamic of the online PPI environment. There were increased opportunities for participation which might encourage the involvement of a broader demographic, and unexpected benefits in that the online platform seemed to have a 'democratising' effect on the meetings, to the benefit of the PPI processes and outcomes. Other studies may however find that their particular research context raises particular challenges for the use of online methods, especially in relation to representation and inclusion, as new barriers to participation may be raised. It is important that methodological challenges are addressed, and researchers provide detailed examples of novel methods for discussion and empirical study. Patient and Public Contribution We report a process which involved people with lived experience of emergency conditions and members of the public. A patient member was involved in the design and implementation, and two patients with lived experience contributed to the manuscript.